The cultural and social dimension of knowledge organization: An discourse analysis of international society for knowledge organization editorials - Evangelista, Isadora Victorino [UNESP]; Bragato Barros, Thiago Henrique [UNESP]; De Moraes, João Batista Ernesto [UNESP] (My University, 2018)
Considering the improve of researches about cultural questions in Knowledge Organization (KO) and the International Society for Knowledge Organization (ISKO) as the most representative institution in studies about KO, queries how the cultural aspects in the area appears and was constructed in the international events of ISKO. To do so, we analyzed the concepts related to this thematic in the editorials published in the events publications. As methodology, was used the Foucault Discourse Analysis, studied by Pêcheux and his group, because it has as characteristic the ideologies rupture and worries in evidence the relations between dominant and dominated. As results, was possible to see that the cultural concepts appears only in the 4th Congress, where was reflects a concern with multicultural and multilingual issues. After this first moment, these questions arise in subthemes, congress themes, round-tables and, in the last Congress, in a dimension dedicated to this universe. As conclusion, was possible to infer that this area of studies is in expansion in the last years, showing that it is not only necessary to the ethical developing of KO, but it is fundamental that researches in this sense increasingly.
Uma anÁLISE do discurso da dimensÃo cultural da ISKO
Keywords: Discourse Analysis; International Society for Knowledge Organization; Knowledge Organization; Sociocultural aspects in KO